PHYSICAL EDUCATION OF STUDENTS WHEN USING ADDITIONAL LESSONS - Щербакова, Елена; Гилев, Геннадий; Гладков, Вадим; Чернов, Юрий (SWorldJournal, 2021)
The overwhelming majority of students entering the first year have poor physical fitness, including those with pathological deviations in health. The study substantiates the expediency of using by students of higher educational institutions additional in